Isolation and Antibiotic Resistant Research of Tetragenococcus halophilus from Xuanwei Ham, A China High-Salt-Fermented Meat Products - Yinjiao Li; Luying Shan; Chen Zhang; Zhan Lei; Ying Shang (MDPI AG, 2019)
We assessed the prevalence of antibiotic resistant and antibiotic resistance genes for 49 Tetragenococcus halophilus (T. halophilus) strains isolated from Xuawei ham in China. The antibiotic resistance phenotype was detected by the Bauer−Kirby (K−B) method and the results showed that 49 isolates can be considered completely susceptible to penicillin, ampicillin, amoxicillin, cefradine, cefotaxime, tetracyclines, minocycline, doxycycline, and vancomycin, but resistant to gentamicin, streptomycin, neomycin, polymyxinB, cotrimoxazole. This resistance was sufficiently high to consider the potential for acquisition of transmissible determinants. A total of 32 isolates were resistant to ofloxacin, 4 isolates were resistant to ciprofloxacin and chloramphenicol, and 2 isolates were resistant to ceftazidime and ticarcillin. The antibiotic resistance genes were detected by routine polymerase chain reaction (PCR). Among the 26 antibiotic resistance genes, 5 varieties of antibiotic resistance genes, including acrB, blaTEM, AAda1, SulII, and GyrB were detected and the detection rates were 89.79%, 47.7%, 16.33%, 77.55%, and 75.51%, respectively. The potential acquisition of transmissible determinants for antibiotic resistance and antibiotic resistance genes identified in this study necessitate the need for a thorough antibiotic resistance safety assessment of T. halophilus before it can be considered for use in food fermentation processes.